MENGHAFAL AL-QUR’AN VIA DARING: Studi Living Qur’an Pada Akun Instagram - Musdalifah; Fairuzah (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract Online tahfidz is a programme for memorizing the Qur'an online, using platforms such as Instagram, WhatsApp, websites, and others. This research aims to answer two queries: First, what motivates the organizers and participants of the online Tahfidz community? Second, what methods are used to memorize the Qur'an online? This qualitative study of the Living Qur'an uses a phenomenological approach and descriptive-analytical methods. The data were collected through interviews, while the informants were the organizers and participants of the online Tahfidz community. The research concludes that the motivation of the online Tahfidz community organizers is as follows: 1) The occurrence of the pandemic, 2) To preach the Qur'an teachings to the wider community, and 3) To redirect the usage of social media away from negative activities. On the other hand, participants' motivations include 1) Utilizing online media and 2) The ease of access to learning. The methods used to memorize the Qur'an include the bin-nazar method, Tahfidz, Takrir, Tasmi', Talaqqi, and Muraja'ah. The research concluded that this online tahfidz is a breakthrough that is effective and desirable amid the rapid development of technology and the busy activities of urban communities. Keywords: Living Qur'an, Qur'an Memorisation, Online